Adaptive Genetic Traits in Human Populations: Evolutionary Responses to Malaria - Arun Ghosh; Aparna Ajith S; Abhijith Pradeep (National Board of Examinations Journal of Medical Sciences)
Malaria continues to be a significant health concern in tropical and subtropical areas. The disease is caused by Plasmodium parasites and spread through mosquito bites. This review investigates the genetic adaptations that humans have developed over time as a response to malaria. Notable adaptations include hemoglobinopathies (sickle cell trait, thalassemias, hemoglobin C), enzyme disorders (G6PD deficiency, pyruvate kinase deficiency), and membrane protein variations (Duffy antigen negativity, hereditary ovalocytosis). These traits disrupt the malaria parasite's life cycle or enhance immune responses, thereby protecting against severe disease. However, they also introduce health risks, such as chronic anemia and complications with certain medications. Future research focuses on gene-editing technologies and new treatments to improve malaria management while addressing these associated health challenges.